Characterizing the Role of Monocytes in T Cell Cancer Immunotherapy Using a 3D Microfluidic Model - Lee, Sharon Wei Ling; Adriani, Giulia; Ceccarello, Erica; Pavesi, Andrea; Tan, Anthony Tanoto; Bertoletti, Antonio; Kamm, Roger Dale; Wong, Siew Cheng (Frontiers in Immunology, 2018)
In the hepatitis-B virus-related hepatocellular carcinoma tumor microenvironment (TME), monocytes reportedly impede natural T cell functions via PD-L1/PD-1 signaling. However, it remains unclear if T cell receptor (TCR)-redirected T cells are similarly inhibited. We thus developed a 3D intrahepatic TME microfluidic model to investigate the immunosuppressive potential of monocytes toward HBV-specific TCR T cells and the role of PD-L1/PD-1 signaling. Interestingly, in our 3D static microfluidic model, we observed that monocytes suppressed only retrovirally transduced (Tdx) TCR T cell cytotoxicity toward cancer cells via PD-L1/PD-1 while mRNA electroporated (EP) TCR T cell cytotoxicity was not affected by the presence of monocytes. Importantly, when co-cultured in 2D, both Tdx and EP TCR T cell cytotoxicity toward cancer cells were not suppressed by monocytes, suggesting our 3D model as a superior tool compared to standard 2D assays for predicting TCR T cell efficacy in a pre-clinical setting, that can thus be used to improve current immunotherapy strategies.